Problem Solving in Foundation Engineering using foundationPro - Yamin, Mohammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is at once a supplement to traditional foundation engineering textbooks and an independent problem-solving learning tool. The book is written primarily for university students majoring in civil or construction engineering taking foundation analysis and design courses to encourage them to solve design problems. Its main aim is to stimulate problem solving capability and foster self-directed learning. It also explains the use of the foundationPro software, available at no cost, and includes a set of foundation engineering applications. Taking a unique approach, Dr. Yamin summarizes the general step-by-step procedure to solve various foundation engineering problems, illustrates traditional applications of these steps with longhand solutions, and presents the foundationPro solutions. The special structure of the book allows it to be used in undergraduate and graduate foundation design and analysis courses in civil and construction engineering. The book stands as valuable resource for students, faculty, and practicing professional engineers. This book also: Maximizes reader understanding of the basic principles of foundation engineering: shallow foundations on homogeneous soils, single piles, single drilled shafts, and mechanically stabilized earth walls (MSE) Examines bearing capacity and settlement analyses of shallow foundations considering varying elastic moduli of soil and foundation rigidity, piles, and drilled shafts Examines internal and external stabilities of mechanically stabilized earth walls with varying horizontal spacing between reinforcing strips with depth Summarizes the step-by-step procedure needed to solve foundation engineering problems in an easy and systematic way including all necessary equations and charts  .
Shallow Foundations on Homogeneous Soil -- Axial Capacity of Single Pile Foundations in Soil -- Axial Capacity of Single Drilled Shaft Foundation in Soil -- Design of Mechanically Stabilized Earth Retaining Walls.
Keywords: Engineering geology; Computer-aided engineering; Buildings -- Design and construction; Mechanics, Applied; Geoengineering; Computer-Aided Engineering (CAD, CAE) and Design; Building Construction and Design; Engineering Mechanics